Aplicação de normativas e tecnologias web para a construção de conteúdos acessíveis - Siena, Frederico de Figueiredo (2013)
There is a collective motion of society with regard to the recognition of the importance of promoting technological and social inclusion of people with special needs. Initiatives in proposing new laws or migrate existing ones pending in the Senate and initiatives such as the Brazilian Electronic Government with well defined policies aim to ensure interoperability between the Government to Citizen. In this work are identified the main actions and technologies capable of providing Accessibility for Web, expanding the possibilities to reach a larger number of people benefit from assistive technologies. Below are the main national laws, treaties, and international standards and recommendations that somehow legally and technical support professionals in the development of new projects or in the migration of existing scenarios. Techniques and scripts are presented, in addition to the application of technologies to the correct semantic markup in web documents, so that the right of access to information available to everyone that the search. Through the survey of technologies and strategies presented here, there is no reason not to propose actions for change towards a more accessible web and the reader at the end of this work will conclude that create and make available content accessible and semantically correct is feasible because there are laws, recommendations, metrics and validators to support and evaluate the effectiveness of web documents. We have identified the importance of well -planned projects under the bias of accessibility and user satisfaction, he has special needs or not, and we contribute with identification of some techniques and metrics established worldwide to apply the concepts of usability that pegged the accessibility, converge in a pleasant experience to users. In research we present some support solutions that bypass some backward compatibility problems found by the majority of web developers with old browsers. With the use of these solutions, strenuous tasks in writing various alternatives for different scenarios are dispensable, or at least minimized. And finally, we present the tests performed with validators, and we comment the behaviour of these same documents submitted to screen readers, which proved the effectiveness of the techniques and solutions presented and conclude the importance of this work in addition to other efforts laudable initiatives in search of citizenship and digital inclusion.